2017
DOI: 10.3390/molecules22050830
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Tormentic Acid, a Major Component of Suspension Cultures of Eriobotrya japonica Cells, on Acetaminophen-Induced Hepatotoxicity in Mice

Abstract: An acetaminophen (APAP) overdose can cause hepatotoxicity and lead to fatal liver damage. The hepatoprotective effects of tormentic acid (TA) on acetaminophen (APAP)-induced liver damage were investigated in mice. TA was intraperitoneally (i.p.) administered for six days prior to APAP administration. Pretreatment with TA prevented the elevation of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin (T-Bil), total cholesterol (TC), triacylglycerol (TG), and liver lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 59 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…The increase of the liver enzymes by high dose of paracetamol is similar to findings of other studies [ 5 20 ]. As albumin is mainly synthesized in the liver, the reduction of serum albumin and total protein by paracetamol overdose is another indication of liver injury.…”
Section: Discussionsupporting
confidence: 91%
“…The increase of the liver enzymes by high dose of paracetamol is similar to findings of other studies [ 5 20 ]. As albumin is mainly synthesized in the liver, the reduction of serum albumin and total protein by paracetamol overdose is another indication of liver injury.…”
Section: Discussionsupporting
confidence: 91%
“…The MAPK pathway consists of three routes viz extracellular regulated kinase (ERK), JNK, and p38MAPK. It is reported that the MAPK pathway is involved in the expression of NF- κ B in the nuclei and subsequent cytokine proteins such as iNOS and COX-2 as well as the pro-inflammatory cytokines such as TNF- α , IL-6, and IL-1 β [ 35 ]. Thus, the effect of Ugonin M on the phosphorylation of ERK, JNK, and p38MAPK was further evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…HO-1 serves as a rate-limiting enzyme that catalyzes heme to antioxidant and anti-inflammatory substances viz biliverdin, carbon monoxide, and iron and subsequently ameliorates symptoms of APAP-induced liver injury [ 35 , 43 ]. The expression of HO-1 will rapidly be up-regulated by oxidative stress conditions such as the administration of APAP [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for 6 days ICR mice, 400 mg/kg i.p. ↑SOD, CAT and GPx;↓NO, TNF-α, IL-1β [52] Methanol extract of Dicranopteris linearis L. leaves 50–500 mg/kg p.o. for 7 days Sprague-Dawley rats, 3 g/kg ↑SOD, CAT [132] Methanol extract of black ginseng 300–600 mg/kg i.g.…”
Section: Targeting Mitochondrial Oxidative Stress and Dysfunction Formentioning
confidence: 99%